PENERAPAN METODE INDEX CARD MATCH PADA PEMBELAJARAN PAI KELAS X DI SMKN 1 TANJUNG RAYA - Fatria Hasnah; Wedra Aprison; Arifmiboy; Charles (KOLONI, 2022)
This research is motivated by the phenomenon of the author's observations about the application of the index card match method with the aim of making students active in participating in learning. However, there are some steps that are left behind and there is no group cooperation in learning. The purpose of this research is to find out how PAI teachers apply the index card match method in class X PAI learning at SMKN 1 Tanjung Raya. This research use desciptive qualitative approach. Collecting research data obtained from interviews and observations. This research was conducted by taking key informants of Islamic Religious Education teachers, and supporting informants of class X TM students, and the principal of SMKN 1 Tanjung Raya. The data analysis technique that the author uses is data reduction, data display and data verification conclusions, and to ensure the validity of this study the author uses data triangulation. From this study, it can be concluded that the teacher applies the index card match method at SMKN 1 Tanjung Raya which includes 3 steps, which consist of introduction, content and closing activities. The first step is to divide the card into two parts consisting of questions and answers, make each question and answer, mix the two sets of cards, then give one card to one student, then instruct students to find their partner cards. The application of the index card match method has been implemented by the teacher well. This can be shown in the application of the index card method to the material that angels are always with me, but there are some steps left by the teacher, namely there are no challenge orders from other students to other pairs, and there are no conclusions from the questions and answers in the index card match method.   Keyword: Application of the Index Card Match Method, PAI Learning